MPLEMENTASI PROGRAM ADIWIYATA MANDIRI DALAM PENINGKATAN PARTISIPASI PEMBELAJARAN LINGKUNGAN HIDUP DI SMP NEGERI 12 SURABAYA - Rica Naudita Krisna Setioningrum; Jojok Mukono (Jurnal Ilmiah Pendidikan Lingkungan dan Pembangunan, 2020)
This research is located at SMP Negeri 12 Surabaya, which is one of the junior high schools that started pioneering for Adiwiyata Schools starting in 2010. The aim of implementing the Adiwiyata program in this school is to create schools that are caring, cultured in the environment and increasing participation in environmental learning. This study has a sub-focus of discussion that has been determined namely the enviromentally sound policies that are applied, the implementation of the environment-based curriculum applied, participatory environment-based activities, management of environmentally friendly supporting descriptive approach. The procedur of collecting research data is observation, in-depth interviews and documentation. Data sources are interviews of adiwiyata team members, team members and teachers. The data analysis of this research used an interactive data analysis model with data collection, data reduction,data presentation and verification. The result of the study showet that the school succeeded in obtainig the Adiwiyata Mandiri school award by forming 15 working groups and establishing 15 activities to support the implementation of the Adiwiyata program. Each working group has minimum of 2 teachers as supervisors and 12 to 20 students. These activities are in the form of takakura waste processing, composter,toga plants, healthy canteen, a clean Friday , 4R (Reuse, Reduce, Recycle, Replace), etc. The program implemented as a strategic program has long-term and sustainable benefit.